Elegy is a Pattern of Western Literature, In Uzbek Literature this Genre is Marsiya (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Elegy is a pattern of Western literature, in Uzbek literature it is controversial to equate this genre with marsiya. In every polar literature there is a period of origin and development of the elegy genre. The marsiya genre entered Uzbek literature as an example of written literature after the 11th century. The elegy genre was introduced by representatives of modern literature in the 20 s of the XX th century. For example, there are excellent examples of this in the works of Abdul hamid Cholpon, Abdurauf Fitrat, Elbek.